The Use of Authentic Materials in Teaching English at Vocational High School - Hikmah Lusian Handayani; Dian Novita Dewi (Universitas Ahmad Dahlan, 2021)
The selection of appropriate teaching materials can be very important to make the student easier in learning English, especially in vocational high school. Teaching English at vocational school is also related to contextual teaching which must be related to the use of materials that are closer to the real world where the learners interact. Therefore, authentic materials become one of the materials that can be used in the teaching-learning process because it is made contextually or is related to real-life material. Additionally, the integration of local content-based materials also provides many benefits for the students in learning English. The goal of this study is to find out teachers’ perceptions on the implementation of authentic materials in English classrooms in vocational high schools. The participants were five English teachers from five vocational high schools located in Pacet, Mojokerto, East Java, Indonesia. The data of this research were gathered using a semi-structured interview. The data analysis technique included data reduction, data display, and drawing conclusions. The result reports that all teachers in vocational high schools in Pacet have positive perceptions of the use of authentic materials in teaching English. It also can be concluded that all the teachers are implemented authentic materials as well as integrate local content in their teaching.